Fatherhood Among Youth Experiencing Homelessness. Issue 4 (October 2020) - Alschech, Jonathan; Begun, Stephanie
Research on young parents experiencing homelessness has typically focused on mothers and pregnant women. Young homeless fathers' tendencies to decline involvement throughout pregnancy and in their children's lives have been documented and condemned; however, little is known about young men's perspectives on these situations. This exploratory study engaged homeless young men in qualitative interviews regarding their perceptions and experiences of fathering. Respondents often viewed fatherhood as solely representing breadwinner responsibilities and as a burden that one dutifully carries or shamefully (yet commonly) shirks. Homeless young men's beliefs about fathering, often steeped in guilt and shame, may suggest that encouraging alternative conceptions of competent fathering while young and homeless is an important area for further research, intervention development, and service provision.